Business and nonproliferation industry's role in safeguarding a nuclear renaissance - Banks, John P.; Ebinger, Charles K. (Washington, D.C. Brookings Institution Press, 2011)
"Forecasts pressure on the fragile nuclear nonproliferation regime because of expected increases in civilian nuclear power nationwide due to global demand and concerns over energy security and greenhouse gas emissions and addresses how the nuclear industry can act as a responsible partner in preventing nuclear weapons proliferation"--Provided by publisher.
Introduction: planning a responsible nuclear energy future / Charles K. Ebinger and John P. Banks -- Nuclear energy and nonproliferation: today's challenges / Sharon Squassoni -- Commercial nuclear markets and nonproliferation / John P. Banks and Sharon Squassoni -- Industry and emerging nuclear energy markets / Charles K. Ebinger and Sharon Squassoni -- Nuclear risks: the views of industry, governments, and nongovernmental organizations / Sharon Squassoni.
Keywords: Nuclear industry; Nuclear energy -- Economic aspects; Nuclear nonproliferation